Can the new French economic policy be successful? - Catherine Mathieu; Henri Sterdyniak (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2013)
In early 2013, the French economy, like many other EU economies, faces tough challenges. French GDP is 9 per cent below the level it would have reached had it continued to grow at its pre-crisis trend. France has committed to cut the public deficit to 3 per cent in 2013 and 0 per cent in 2017 which would imply dramatic public spending cuts and fiscal tightening, reducing GDP growth even further. France has to choose between strengthening its specificity, its social model and its State-interventionist tradition, and imitating the best pupils of globalization in the world or in Europe by implementing liberal or social-liberal strategies. The paper deals with the French government strategy since the 2012 presidential elections and tries to assess its chances of success. In many areas – fiscal strategy, social issues, banking and industrial policies – there is a significant risk that the announced proactive strategy will be replaced by policies accepting the constraints imposed by European institutions and financial markets.
Keywords: E65; H60; 330; French economic policy; fiscal compact